ESL METHODOLOGY AS AN ASPECT OF BILINGUAL EDUCATION - Ivanova, Y. S.; Paul, L. Y.; Tyulyubayeva, G. S. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article is about the basic concepts of bilingualism and features of a communicative technique ESL (English as a Second Language) are considered. ESL is the technique developed by the American linguists and recognized as the most effective for comprehensive study of English. In literal translation of ESL is – «English as the second native language». The principle of studying is based on gradual complication of material «from simple - to difficult».
Keywords: bilingual education; English as a Second Language; anguage skills; communication; language development